2010
DOI: 10.1108/00251741011068806
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents of response strategies in strategic alliances

Abstract: Purpose -Strategic alliances involve uncertainty, interdependence, and vulnerability, which often create adverse situations. This paper seeks to understand how alliance managers respond to these adverse situations by examining the influence of four exchange variables on response strategies. Design/methodology/approach -A scenario-based experiment provides empirical support for a typology consisting of seven conceptually and empirically distinct response strategies: exit, opportunism, aggressive voice, creative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(84 citation statements)
references
References 71 publications
1
80
1
1
Order By: Relevance
“…Opportunism also joins the typology as an active-destructive strategy (Ping, 1993). Thus, seven response strategies appear in previous literature: exit, opportunism, aggressive voice, creative voice, considerate voice, patience, and neglect (Tjemkes and Furrer, 2010).…”
Section: Response Strategiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Opportunism also joins the typology as an active-destructive strategy (Ping, 1993). Thus, seven response strategies appear in previous literature: exit, opportunism, aggressive voice, creative voice, considerate voice, patience, and neglect (Tjemkes and Furrer, 2010).…”
Section: Response Strategiesmentioning
confidence: 99%
“…Over time, their investment model has been tested empirically in several contexts, including job satisfaction (Rusbult and Farrell, 1983;Rusbult et al, 1988), romantic relationships (Rusbult and Zembrodt, 1983), channel relationships (Geyskens and Steenkamp, 2000;Ping, 1993), and strategic alliances (Tjemkes and Furrer, 2010). Among these studies those focusing on alliances identified four exchange variables that influence preferences for response strategies: economic satisfaction, social satisfaction, alternative attractiveness, and alliance-specific investments.…”
Section: Adverse Situations and Exchange Variablesmentioning
confidence: 99%
See 3 more Smart Citations